The effects of curcumin supplementation added to diet on anthropometric and biochemical status in women with polycystic ovary syndrome: A randomized, placebo-controlled trial - Asan, Sabiha Ataç; Baş, Murat; Eren, Berna; Karaca, Esen (Progress in Nutrition, 2021)
Clinical manifestations of polycystic ovary syndrome (PCOS) include infrequent or absent menses, abdominal obesity, acanthosis nigricans and signs of androgen excess which include acne or seborrhea and insulin resistance. We hypothesized that curcumin added to diet would modulate anthropometric and biochemical status in women with PCOS.  This study was performed with the participation of 30 individuals diagnosed with PCOS by physicians. Participants were randomly assigned to curcumin (at a dose of 93.34 mg) or placebo groups.  After a period of eight weeks,  body weight, body fat mass and waist circumferences (WC) were found  lower in the curcumin group than the placebo group (p